2017
DOI: 10.18632/oncotarget.23721
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a small molecule R-spondin-1 substitute RS-246204 on a mouse intestinal organoid culture

Abstract: Organoids, a multi-cellular and organ-like structure cultured in vitro, can be used in a variety of fields such as disease modeling, drug discovery, or cell therapy development. When organoids derived from Lgr5 stem cells are cultured ex vivo, recombinant R-spondin-1 protein should be added at a high concentration for the initiation and maintenance of the organoids. Because the addition of large amounts of R-spondin-1 greatly increases the cost of organoids, the organoids grown with R-spondin-1 are not practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…To support the development of intestinal organoids, medium is typically supplemented with EGF, Noggin, Wnt3a, and R-spondin (Holmberg et al, 2017). However, small molecule-based approaches that replace Wnt-3a with Chir99021 (Langlands et al, 2018;, Noggin with LDN-193189 (Liu et al, 2018b), and R-spondin with RS-246204 (Nam et al, 2017) have been presented. Single cells first grow into 3D Human Tissue Models cyst-like aggregates, which upon prolonged culture assume a budding-like morphology.…”
Section: Intestinal Organoid Culturesmentioning
confidence: 99%
“…To support the development of intestinal organoids, medium is typically supplemented with EGF, Noggin, Wnt3a, and R-spondin (Holmberg et al, 2017). However, small molecule-based approaches that replace Wnt-3a with Chir99021 (Langlands et al, 2018;, Noggin with LDN-193189 (Liu et al, 2018b), and R-spondin with RS-246204 (Nam et al, 2017) have been presented. Single cells first grow into 3D Human Tissue Models cyst-like aggregates, which upon prolonged culture assume a budding-like morphology.…”
Section: Intestinal Organoid Culturesmentioning
confidence: 99%
“…In addition, neuregulin 1 (NRG1), a key EGF family ligand produced by mesenchymal stromal cells, macrophages, and Paneth cells, is important for the proliferation of intestinal crypts and organoid formation, as well as for regeneration after injury [29]. A recent study also demonstrated that R-spondin 1 could be substituted by a compound named RS-246204 for mouse intestinal organoid culture [30]. Moreover, the modulation of Wnt and Notch signaling in intestinal organoids can regulate IEC lineage differentiation [31].…”
Section: Intestinal Organoids As a Tool For Understanding Gi Biologymentioning
confidence: 99%
“…It was demonstrated that the addition of DAPT or BMP molecules to the culture medium is sufficient to stimulate the differentiation of ISCs and the generation of multicellular intestinal organoids. Moreover, some studies have been carried out to search for methods to reduce the cost of culture media, which reported that the Noggin protein can be replaced by LDN-193189, and R-spondin 1 protein can be substituted by RS-246204 (Liu et al 2018;Nam et al 2018;Rahmani et al 2019).…”
Section: Intestinal Organoidsmentioning
confidence: 99%